(untitled) (Marketing Journal, 2026)
Abstract The study identified mechanisms for evaluating the impact of regional innovation infrastructure on economic development. An integral RII index was developed, covering research environment, financial mechanisms, technology parks, digital infrastructure, and human capital. The indicators were standardized using the min–max normalization method, and weight coefficients were determined based on expert assessment. Panel data regression analysis was applied to evaluate the relationship between the index and economic growth indicators. The empirical analysis was conducted using regional statistical data of Uzbekistan. The results revealed significant differences in the level of innovation infrastructure development across regions. The proposed methodology served as a practical tool for monitoring regional innovation performance and supporting evidence-based investment and management decisions. Keywords: regional innovation infrastructure, RII index, economic development, panel data, Uzbekistan.